DIVIDEND POLICY AND PROFITABILITY: AN EMPIRICAL ANALYSIS OF COMPANIES LISTED ON THE IDX - Yulianti, Maria Lusiana; Purnomo, Budi Supriatono; Purnamasari, Imas; Sari, Maya (Jurnal Riset Bisnis dan Manajemen, 2026)
This study investigates the relationship between dividend policy and profitability among companies listed on the Indonesia Stock Exchange (IDX) during 2020-2024. Employing panel data analysis on manufacturing and service sector firms, this research examines how profitability metrics influence dividend payout decisions. The findings reveal significant positive relationships between ROA, ROE, and dividend payout ratios, supporting signaling theory. Firm size, leverage, and free cash flow are identified as important determinants of dividend policy. Results provide valuable insights for investors, managers, and policymakers, suggesting that profitable firms distribute higher dividends to signal financial strength and reduce agency conflicts.